Driving Sustainable Competitiveness through Market and Technology Orientation in Coffee Shops - Hanif Shidqi; Desman Hidayat (APPS Publications, 2026)
This research aims to determine the influence of market orientation and technology orientation on sustainable competitive advantage with product innovation (directly or as a mediating variable). This study deployed a quantitative, explanatory survey design analyzing data from 63 Indonesian consumers who engaged with TikTok Live using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The structural framework evaluated dual information-processing routes (specifically central-route argument quality, peripheral-route streamer credibility and attractiveness, and interactive engagement) to test their direct impacts on purchase intention. The test results prove that market orientation and technology orientation have a positive and significant influence on sustainable competitive advantage with product innovation (directly or as a mediating variable) in coffee shops in Jabodetabek. Grounded in the Elaboration Likelihood Model (ELM), this study addresses existing contradictions in social commerce literature by empirically isolating how dual information-processing routes (central route argument quality versus peripheral route credibility and attractiveness) and real-time interactivity function together within the rapidly growing, highly interactive TikTok Shop live-streaming ecosystem in Indonesia.